Post-WBRT cognitive impairment and hippocampal neuronal depletion measured by in vivo metabolic MR spectroscopy: Results of prospective investigational study - Pospisil, Petr; Kazda, Tomas; Hynkova, Ludmila; Bulik, Martin; Dobiaskova, Marie; Burkon, Petr; Laack, Nadia N; Slampa, Pavel; Jancalek, Radim (Radiotherapy and oncology, 2017)
BACKGROUND AND PURPOSE: The aim of this prospective study is to evaluate post-whole brain radiotherapy (WBRT) changes in hippocampal concentration of N-acetylaspartate (h-tNAA) as a marker of neuronal loss and to correlate those changes to neurocognitive function. MATERIAL AND METHODS: Thirty-five patients with brain metastases underwent baseline single slice multi-voxel MR spectroscopy (MRS) examination for measurement of hippocampal h-tNAA together with baseline battery of neurocognitive tests focused on memory (Auditory Verbal Learning Test and Brief Visuospatial Memory Test - Revised) as well as quality of life questionnaires (EORTC QLQ-C30 a EORTC QLQ-BN20). Eighteen patients completed follow-up evaluation four months after standard WBRT (2 laterolateral fields, 10×3.0Gy, 6MV photons) and were included in this analysis. MRS and cognitive examinations were repeated and compared to baseline measurements. RESULTS: Statistically significant decreases in h-tNAA were observed in the right (8.52-7.42mM; -12.9%, 95%CI: -7.6 to -16.4%) as well as in the left hippocampus (8.64-7.60mM; -12%, 95%CI: -7.9 to -16.2%). Statistically significant decline was observed in all AVLT and BVMT-R subtests with exception of AVLT_Recognition. Quality of life declined after WBRT (mean Δ -14.1±20.3 points in transformed 0-100 point scale; p=0.018) with no correlation to changes in hippocampal metabolite concentrations. Moderate positive correlation was observed between left h-tNAA concentration decrease and AVLT_TR decline (r=+0.32; p=0.24) as well as with AVLT_DR (r=+0.33; p=0.22) decline. Changes in right h-tNAA/Cr negatively correlated with AVLT_DR (r=-0.48; p=0.061). No correlation between right hippocampus h-tNAA and memory decline (AVLT) was observed. CONCLUSIONS: Our results suggest hippocampal NAA concentrations decline after WBRT and MRS may be a useful biomarker for monitoring neuronal loss after radiotherapy.
Keywords: Brain Neoplasms; Male; kvalita života; biologické markery; Quality of Life; Biomarkers; Neurocognitive function; následné studie; nádory mozku; kognitivní dysfunkce; Nerve Degeneration; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Prospective Studies; mužské pohlaví; Cognitive Dysfunction; průzkumy a dotazníky; Aspartic Acid; Follow-Up Studies; Neuropsychological Tests; Hippocampus; degenerace nervu; kyselina asparagová; Magnetic resonance spectroscopy; lidé; Cranial Irradiation; ženské pohlaví; Humans; kraniální ozáření; paměť; Memory; neuropsychologické testy; Radiation injury; Female; Surveys and Questionnaires; lidé středního věku; hipokampus; Middle Aged; prospektivní studie